Interclonal Hybridization studies in Banana - Krishnakumar MP (Department of Pomology, Floriculture and Landscapping, College of Horticulture, 1987)
Investigations were carried out on the interclonal hybridization in banana, involving six female parents, viz: ‘Palayankodan’, ‘Rasthali’, ‘Nendravannan’, ‘NeyPoovan’, ‘Karpooravally’ and ‘Nendran’ and three male parents, viz: ‘Pisang Lilin”, Tongat’ and ‘Sanna chenkadali’, with a view to make a detailed study on pollen production, fertility and viability in different nodes of the male parents and female fertility pattern in different hands of the six female parents, compatibility and seed set in 18 cross combinations involving six female parents and three male parents, effect of different seed treatment on germination of banana seeds and evaluation of existing interclonal hybrids already available, in the Department of Pomology and Floriculture, College of Horticulture during the year 1985-86. Pollen production, fertility and viability studied in the three male parents, viz: ‘Pisang Lilin’, ‘Tongat’ and ‘Sanna Chenkadali’ revealed that there was marked variation among the parents in all these pollen characters. Within each parent, all these characters varied greatly with the age of bud. ‘pisang Lilin’ recorded the maximum pollen production per anther (8431.12) and highest pollen fertility (53.74 per cent). The pollen production varied from 3875.41 in the 1st node to 947.14 in the 55th node and fertility from 46.14 per cent in the 1st node to 28.45 per cent in the 55th node, with the maximum pollen production and fertility in the 25th and 20th nodes. In ‘Sanna Chenkadali’, the maximum pollen production and fertility were obtained in the 27th and 28th nodes and in ‘Tongat’ in the 20th and 16th nodes respectively. Standardisation of media for pollen germination and tube growth indicated that a medium consisting of 35 per cent sucrose was the best. The germination of pollen grains was found to be maximum after 24 hours of dusting on the medium. The pollen viability in terms of germination per cent and tube growth was also found to be maximum in ‘Pisang Lilin’ which varied between 19.63 in the 1st node to 6.14 in the 50th node, with a maximum of 31.15 in the 15th node. The pollen tube length varied between 210.12 µ in the 1st node to 112. 40 µ in the 50th node, with a maximum tube length of 410.83 µ in the 25th node. Out of the 18 cross combinations studied, only 3 combinations, involving, ‘Palayankodan’, ‘Rasthali’ and ‘Nendran’ as female parents and ‘Pisang lilin’ as male parent were compatible. Among the three male parents used for hybridization, only ‘Pisang Lilin’ was found to be compatible with the fertile female parents. Seed production was found to be maximum in ‘Palayankodan’ (102.96 seeds per bunch). ‘Rasthali’ produced the least number of seeds per bunch (10.98). The fertility patteren with respect to position of hands in a bunch showed variation. In ‘Palayankodan’, fertility was maximum in the third hand (27.33), while in ‘Nendran”, second hand was more fertile (7.00). ‘Rasthali’ produced maximum number of seeds in second and third hands (2.66). Among the various seed treatments tried, only two seeds subjected to acid treatment, from the cross ‘Palayankodan’ x ‘Pisang Lilin’ germinated. However, the treatments were not found to be effective. The three hybrids from cross, ‘Agniswar’ x ‘Pisang Lilin’, were found to be triploids (2n = 33) with AAB genomic group. With respect to various growth parameters, duration aspects, bunch characters, finger characters and quality aspects, the three hybrids differed significantly between parents and also among themselves. Among the hybrids, ‘Hybrid No. 111” was superior in characters such as height (285.00 cm), number of functional leaves (8.33), leaf area (9.3 M2), petiole length (47.66 cm), bunch yield (9.10 kg), number of hands (7.00), number of fingers (95.00) and quality aspects, viz: total soluble solids (21.17 per cent) and total sugars (15.5 per cent), to both the parents and other two hybrids. The hybrids were found to be male fertile n pollen studies and female fertile on artificial pollination, excepting ;Hybrid No. 11’which was only male fertile. However, hybrids were inferior in pollen production, fertility and viability as compared to the paternal parent and poor in seed yield as compared to the maternal parent.